Evaluasi Proses Pengadaan dan Distribusi Logistik Non Medis di Rumah Sakit Umum Pusat Dr. Hasan Sadikin Bandung - Aditya Rizky Permana; Bunga Diana (Jurnal Infokes, 2026)
This study aims to evaluate the effectiveness and efficiency of non-medical logistics procurement and distribution amid the current budget efficiency policy. Non-medical logistics, such as office supplies, printing materials, general merchandise, and other basic necessities, play a crucial role in ensuring the smooth operation of services within each institution, particularly in the healthcare sector. The study was conducted at Dr. Hasan Sadikin General Hospital in Bandung from March to May 2025, using a qualitative approach through semi-structured interviews and document analysis with relevant institutions. The study involved four informants, including procurement officials, logistics staff, and representatives from goods supply service units. The evaluation findings revealed that despite budget cuts, inter-agency coordination and the use of digital systems in procurement and distribution have helped reduce waste and accelerate distribution processes. However, several challenges remain, such as data discrepancies between inventory and actual needs, which hinder logistics operations. This study includes strengthening the integrated monitoring system, simplifying procurement procedures, and optimizing periodic mapping to ensure the accuracy of non-medical logistics distribution targets.